5 - Transfert de technologie et perspectives internationales de développement en Afrique Sub Saharienne: Quelques reflexions - Maurice Kamto, (Africa Development, 1987)
One finds an avalanche of studies on the transfer of technology. Of these% very few have focussed on Africa. The article addresses itself to this lacuna by pointing the significance and scope of new data on the transfer of technology in Sub-Saharan Africa. Is there any hope that Sub-Saharan Africa will take advantage of the transfer of technology to promote its own development? Such a simple question calls for a complex answer. Technology is a component of the modern state power and indeed a necessity for the development of African countries. However technology is too expensive a commodity for most Sub-Saharan African countries. Nonetheless Africa is a major consumer continent and suppliers can therefore increase the technological dependence of Africa by selecting the technologies to be transferred and thus establishing a new international division of labour based on the contrast generators producers and reproducers/consumers of technology. Such an awareness leads to the following reflection the major parts of which are: I. Transfer of technology appears as a strong necessity with a two-fold implication. Indeed, the prospects of modern economy and better living conditions it offers make it a catalyst of development on the one hand while on the other hand it also acts as a new factor of dependence especially in Sub-Saharan Africa which is at the periphery of technology producing centres. II. This transfer toward Sub-Saharan Africa and on a larger scale toward the Third World is however hampered by the scope of the technological stake for two reasons. One, technology is a major profit making factor of multinational corporations and, as such, constitutes a corner-stone in their world strategies; two, it now appears as an element of power of industrialized countries, becoming therefore crucial in their strategies of foreign policy. These countries and their companies have taken a stance which can be summed up as "One Japan is enough". III. Nevertheless a number of strategies are still open to Africa. These may be based on the experience of Third World countries like China, Brazil, the Republic of Korea, Argentina, India, Mexico etc. which have apparently found their own course or on a Promethean strategy geared toward the development of national technological capacities. Such a development could be achieved by sending abroad scientists with a strong local training background to embark on the study of science and technology wherever such a training is available, just as Prometheus stole fire from heaven. There will be other Japans!